High-density multi-component L12 phase reinforced Cu-based alloy water electrolysis catalyst and preparation method and application thereof
By designing a high-density multi-component L12 phase-strengthening Cu-based alloy electrolytic catalyst, the existing catalysts have insufficient conductivity and inability to self-carry their form during the electrolytic hydrogen production process, and the excellent catalytic efficiency and electrochemical stability of the catalyst are achieved.
Patent Information
- Application Number
- CN202510091417.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing catalysts have problems such as insufficient conductivity, inability to self-carry and poor electrochemical stability in the process of electrolyzing hydrogen production, which limits their wide application in industrial electrolyzing water.
A high-density multi-component L12 phase-strengthening Cu-based alloy electrolytic catalyst was designed, and an L12 phase structure with excellent conductivity and catalytically active adsorption sites was formed through reasonable component design and heat treatment process.
The excellent catalytic efficiency, electrochemical stability and ultra-high strength of the catalyst are achieved, and the dependence on current collectors and layer support is avoided. The process controllability is strong and the processing quality is high.
Smart Images

Figure CN119913411A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] Hydrogen is a clean, efficient, and widely available secondary green energy carrier. It boasts high energy density, clean combustion products, and is renewable and easily storable. Vigorously developing hydrogen energy is an inevitable trend in the future energy structure upgrade and transformation. While hydrogen offers numerous advantages over other energy sources, achieving large-scale, efficient, and low-cost hydrogen production and safe storage still faces numerous challenges.
[0003] Electrochemical water splitting for hydrogen production is a relatively mature technology with simple operation and high efficiency. Among them, the catalyst for the oxygen evolution reaction in water electrolysis is a key material for improving the level of hydrogen production and directly determines the efficiency of hydrogen production. High-efficiency electrocatalysts generally need to have good conductivity, abundant active sites, and excellent electrochemical stability. Currently, commonly used catalysts include precious metal catalysts such as IrO2 and RuO2, transition metal-based catalysts such as CuO and NiO, and high-entropy alloy catalysts. Studies on Ni-based, Co-based, Fe-based, and some precious metal-containing binary or ternary alloy catalysts have shown that although these catalysts exhibit excellent electrocatalytic performance, some alloy catalysts are limited by their morphology, such as the inability to be self-supporting and insufficient conductivity, resulting in the need for stable electrocatalytic function with the assistance of a current collector, which hinders their widespread application in industrial water electrolysis. At the same time, precious metal alloys are generally expensive and scarce, which limits their practical application.
[0004] Multi-component alloys can achieve comprehensive improvements in alloy performance through reasonable composition design and organizational regulation, while also regulating the electronic and geometric structures of catalysts to a great extent, and providing a good platform for constructing catalysts with unexpected properties. To date, there have been many attempts in the research field of developing high-efficiency electrocatalyst materials, but how to screen and design catalysts with reasonable prices, high efficiency and long-term stability from abundant metal elements remains a difficult problem to be solved. Cu has excellent electrical conductivity, but its adsorption performance for hydrogen and oxygen is poor. Therefore, exploring and designing a new catalytically integrated alloy Cu-based electrode material with excellent electrical conductivity and long-term stability is of great significance to promoting the development of the field of electrocatalytic water splitting. Summary of the Invention
[0005] In order to solve the above technical problems, the present invention proposes a high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst and its preparation method and application.
[0006] To achieve the above objectives, the present invention provides the following technical solutions:
[0007] The invention provides a high-density multi-component L12 phase reinforced Cu-based alloy water electrolysis catalyst, which comprises the following components in atomic percentage: 49.9% Cu, 18% Ni, 18% Co, 9% Al, 3% Ti, 1.4% Cr, 0.3% Nb, 0.3% V and 0.1% B.
[0008] Preferably, the grains of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst are equiaxed crystals with a grain size of 0.5-2 μm.
[0009] Preferably, the high-density multi-component L12 phase reinforced Cu-based alloy water electrolysis catalyst includes L12 phase, and the volume fraction of the L12 phase is 50%.
[0010] Preferably, the composition formula of the L12 phase is (Cu, Ni, Co)3(Al, Ti, Cr, Nb, V); the L12 phase exists in two different sizes, which are 100-300 nm and 5-10 nm respectively.
[0011] The present invention provides a preparation method of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst described in the above technical solution, comprising the following steps: weighing raw materials according to atomic percentage, mixing the raw materials, and then smelting, heat treating, hot rolling, cold rolling and aging treatment to obtain the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst.
[0012] Preferably, the heat treatment temperature is 1070° C. and the time is 6 hours.
[0013] Preferably, the hot rolling temperature is 1050° C., the reduction per pass is 1 mm, and the cumulative deformation is 80%.
[0014] Preferably, the cold rolling temperature is room temperature, the reduction per pass is 0.5 mm, and the cumulative deformation is 50%.
[0015] Preferably, the aging treatment temperature is 900° C., the time is 1 hour, and the cooling method is furnace cooling.
[0016] The present invention also provides the use of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst described in the above technical solution in hydrogen production by water electrolysis.
[0017] Technical Principle: The present invention uses Cu as the matrix, adding Ni and Al elements to cause the precipitation of L12 phase in the alloy. Co is introduced to replace part of Ni to further enhance the catalytic performance of the L12 phase. By adding Ti in place of Al, the precipitation of L12 phase is promoted and the brittleness of the alloy is reduced, thereby ensuring processing performance. The addition of refractory elements such as Nb and V can enhance the stability of the L12 phase and prevent its coarsening during aging. The addition of Cr ensures the electrochemical stability of the alloy through the formation of a Cr2O3 passivation layer. B is a small interstitial atom that easily segregates at grain boundaries, enhancing grain boundary strength, further optimizing the mechanical properties of the alloy, and ensuring its processing performance. Ultimately, by rationally designing the composition to regulate the element distribution in the precipitate phase and the matrix phase, a high-density, multi-component L12 phase-reinforced Cu-based alloy was obtained.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] The present invention starts from the perspective of enthalpy interaction between elements and obtains a high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst. The catalyst uses Cu as the matrix, which ensures the conductive performance of the alloy. Through reasonable component design, the high-density multi-component L12 phase is precipitated, providing more catalytically active adsorption sites, ensuring the excellent catalytic performance of the Cu-based alloy. At the same time, the reasonable component design also makes the alloy have excellent electrochemical stability, ultra-high strength and machinability, effectively solving the limitations of existing catalyst forms such as the inability to be self-supporting and insufficient conductivity.
[0020] The high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst provided by the present invention has excellent catalytic efficiency, electrochemical stability and ultra-high strength, does not require any current collector and layer carrier, has strong process controllability and high processing quality, and is of great significance for improving energy conversion efficiency and accelerating the electrocatalytic reaction kinetics process.
[0021] The performance indicators of the high-density multi-component L12 phase reinforced Cu-based alloy water electrolysis catalyst provided by the present invention are: conductivity 5.5% IACS, hardness 350HV, ultimate tensile strength 1100MPa, current density 10mA / cm 2 and 50mA / cm 2 The overpotentials were 0.351 V and 0.429 V respectively, the Tafel slope was 75 mV / dec, and the electrochemical stability reached 110 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which constitute part of the present invention, are provided to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are provided to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0023] Figure 1The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 X-ray diffraction pattern of;
[0024] Figure 2 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 Metallographic organization diagram;
[0025] Figure 3 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 TEM bright field image and element distribution map;
[0026] Figure 4 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 Linear sweep voltammetry curve in 1 mol / L KOH solution;
[0027] Figure 5 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 Tafel slope in 1 mol / L KOH solution;
[0028] Figure 6 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 Electrochemical stability in 1 mol / L KOH solution. DETAILED DESCRIPTION
[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] An embodiment of the present invention provides a high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst, which includes the following components in atomic percentage: Cu 49.9%, Ni 18%, Co 18%, Al 9%, Ti 3%, Cr 1.4%, Nb 0.3%, V 0.3% and B 0.1%.
[0032] The present invention regulates the element distribution in the precipitated phase and the matrix phase through reasonable composition design, thereby obtaining a high-density multi-component L12 phase-reinforced Cu-based alloy with excellent catalytic efficiency, electrochemical stability and ultra-high strength.
[0033] In a preferred embodiment, the high-density multi-component L12 phase reinforced Cu-based alloy water electrolysis catalyst has equiaxed grains with a grain size of 0.5-2 μm. The equiaxed grains in the alloy help improve the electrical conductivity and strength of the alloy.
[0034] In a preferred embodiment, the high-density, multi-component L12-phase-reinforced Cu-based alloy water electrolysis catalyst includes an L12 phase having a volume fraction of 50%. The precipitation of the high-density, multi-component L12 phase provides more catalytically active adsorption sites, ensuring the excellent catalytic performance of the Cu-based alloy.
[0035] In a preferred embodiment, the composition formula of the L12 phase is (Cu, Ni, Co)3(Al, Ti, Cr, Nb, V); the L12 phase exists in two different sizes, which are 100-300 nm and 5-10 nm respectively.
[0036] The present invention provides a preparation method of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst described in the above technical solution, comprising the following steps: weighing raw materials according to atomic percentage, mixing the raw materials, and then smelting, heat treating, hot rolling, cold rolling and aging treatment to obtain the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst.
[0037] In a preferred embodiment, the purity of the raw material is 4N or above.
[0038] In a preferred embodiment, the smelting method is non-consumable vacuum arc melting, the smelting atmosphere is argon; the smelting current is 220-250A, and the number of smelting times is 5;
[0039] In a preferred embodiment, the heat treatment temperature is 1070° C. and the treatment time is 6 hours. The present invention controls the heat treatment temperature and treatment time within the above ranges to ensure that the strengthening phase in the Cu-based alloy is mainly the L12 phase.
[0040] In a preferred embodiment, the hot rolling temperature is 1050° C., the reduction per pass is 1 mm, and the cumulative deformation is 80%.
[0041] In a preferred embodiment, the cold rolling temperature is room temperature, the reduction per pass is 0.5 mm, and the cumulative deformation is 50%.
[0042] In a preferred embodiment, the aging treatment is carried out at a temperature of 900° C. for 1 hour, and the cooling method is furnace cooling.
[0043] The present invention also provides the use of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst described in the above technical solution in hydrogen production by water electrolysis.
[0044] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0045] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0046] Example 1
[0047] A method for preparing a high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst, comprising the following steps:
[0048] The composition is Cu 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1The invention relates to a method for preparing a Cu-based water electrolysis catalyst Cu-2+ alloy by converting the (at.%) alloy into weight percentage, and preparing raw materials of Cu, Ni, Co, Al, Ti, Cr, Nb, V and B with a purity of 4N or more; adopting non-consumable vacuum arc melting, introducing argon as a protective gas, and repeatedly melting the above-mentioned raw materials 5 times at a melting current of 220A to obtain a cast alloy ingot; keeping the obtained cast alloy ingot at 1070°C for 6 hours, air cooling, and obtaining a heat-treated alloy ingot; subsequently, hot rolling the heat-treated alloy ingot at 1050°C, with a reduction of 1 mm per pass and a cumulative deformation of 80%; then, cold rolling the hot-rolled alloy at room temperature, with a reduction of 0.5 mm per pass and a cumulative deformation of 50%; then, aging treatment is performed on the cold-rolled alloy, the aging treatment temperature is 900°C, the time is 1 hour, and the cooling method is furnace cooling, and finally a high-density multi-component L12 phase-reinforced Cu-based alloy electrolysis catalyst Cu-2+ alloy is obtained. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 .
[0049] The Cu prepared in Example 1 was tested at room temperature. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The electrical conductivity measured by eddy current conductivity meter is 5.5% IACS, the hardness measured by Vickers hardness tester is 350HV, and the ultimate tensile strength measured by universal tensile testing machine is 1100MPa.
[0050] The Cu prepared in Example 1 was measured using a German Bruker D8 FOCUS X-ray diffractometer. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 X-ray diffraction analysis was performed, and the results are shown in Figure 1 .from Figure 1 It can be seen that the heat-treated alloy ingot obtained in Example 1 contains an FCC structure Cu-based solid solution and an L12 phase structure.
[0051] Figure 2 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb0.3 V 0.3 B 0.1 From the metallographic structure diagram. Figure 2 It can be seen from the figure that the alloy grains are equiaxed and the size is 0.5-2μm.
[0052] Figure 3 The Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 TEM bright field image and element distribution map, the left picture is TEM bright field image, the right picture is element distribution map. Figure 3 The TEM bright field image shows that there is a high-density coherent precipitated multi-component L12 phase in the crystal. The size of the L12 phase is 100-300nm and 5-10nm. The 100-300nm L12 phase exists at the grain boundary. It can also be seen that the composition formula of the L12 phase is Cu 11.5 Ni 30.02 Al 14.83 Co 33.22 Cr 2.49 Ti 6.85 Nb 0.45 V 0.64 .from Figure 3 It can be seen from the element distribution diagram in that the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst prepared in Example 1 contains Cu, Ni, Co, Al, Ti, Cr, Nb, V, and B.
[0053] Electrochemical performance test:
[0054] The test was carried out in a 1 mol / L KOH solution using a three-electrode system, with a graphite electrode as the counter electrode and a mercury / mercurous oxide electrode as the reference electrode. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The linear sweep voltammetry test was performed at room temperature with a scan rate of 0.05 mV / s. The test results are shown in Figure 4 .from Figure 4 It can be seen that the Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1At a current density of 10 mA / cm 2 and 50mA / cm 2 The overpotentials are 0.351V and 0.429V respectively.
[0055] The Cu prepared in Example 1 was obtained by fitting the linear voltammetric curve. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The Tafel slope in 1 mol / L KOH solution is shown in the following table. Figure 5 .from Figure 5 It can be seen that the Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The Tafel slope is 75mV / dec.
[0056] The Cu prepared in Example 1 was tested at room temperature. 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The electrochemical stability in 1 mol / L KOH solution is shown in Figure 6 .from Figure 6 It can be seen that the Cu prepared in Example 1 49.9 Ni 18 Co 18 Al9Ti3Cr 1.4 Nb 0.3 V 0.3 B 0.1 The electrochemical stability can reach 110h.
[0057] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst, characterized in that: In atomic percentage, it includes the following components: Cu 49.9%, Ni 18%, Co 18%, Al 9%, Ti 3%, Cr 1.4%, Nb 0.3%, V 0.3% and B 0.1%.
2. The high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst according to claim 1, characterized in that: The crystal grains of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst are equiaxed crystals, and the crystal grain size is 0.5-2 μm.
3. The high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst according to claim 1, characterized in that: The high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst comprises an L12 phase, and the volume fraction of the L12 phase is 50%.
4. The high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst according to claim 3, characterized in that: The composition formula of the L12 phase is (Cu, Ni, Co)3(Al, Ti, Cr, Nb, V); the L12 phase exists in two different sizes, which are 100-300nm and 5-10nm respectively.
5. The method for preparing the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials are weighed according to atomic percentage, mixed, and then smelted, heat treated, hot rolled, cold rolled and aged to obtain the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst.
6. The preparation method according to claim 5, characterized in that: The heat treatment temperature is 1070° C. and the time is 6 hours.
7. The preparation method according to claim 5, characterized in that: The hot rolling temperature is 1050° C., the reduction in each pass is 1 mm, and the cumulative deformation is 80%.
8. The preparation method according to claim 5, characterized in that: The cold rolling temperature is room temperature, the reduction amount per pass is 0.5 mm, and the cumulative deformation amount is 50%.
9. The preparation method according to claim 5, characterized in that: The aging treatment is carried out at a temperature of 900° C. for 1 hour, and the cooling method is furnace cooling.
10. Use of the high-density multi-component L12 phase-reinforced Cu-based alloy water electrolysis catalyst according to any one of claims 1 to 4 in electrocatalytic water decomposition.